ANALISIS KEMAMPUAN MEMBACA PERMULAAN PADA ANAK FASE A SEBAGAI FONDASI MEMBANGUN LITERASI NUMERASI: STUDI ETNOGRAFI DI SD NEGERI SARIREJO 1 - Arnita, Sinta; Purnamasari , Iin; Rofian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the suboptimal reading skills of phase A children. This is evidenced by the results of the education report card of SD Negeri Sarirejo 1 in 2024, where children's literacy and numeracy skills in several aspects have decreased scores from last year. This study used a qualitative approach with ethnographic methods. Data collection used observation, interview and documentation techniques. The results showed that (1) children in phase A of SD Negeri Sarirejo 1 still experience difficulties, such as: mispronouncing words, spelling repeatedly, difficulty combining consonant letters such as "-ng", not paying attention to punctuation, lack of confidence, misunderstanding similar numbers such as "12" and "21", not yet able to analyze information from the table because they make mistakes in addition when calculating data, (2) inhibiting factors are physiological factors in the form of fatigue and lack of nutritional intake, psychological factors including children's interest, motivation, and mental readiness, and environmental factors in the form of teacher influence and parental encouragement, (3) the teacher's strategy to overcome these problems is to use learning media in the form of illustrated reading books that contain visual elements, letters, words, tables, and simple diagrams, (4) the ethnographic pattern at SD Negeri Sarirejo 1 shows that early reading ability as a foundation for building numeracy literacy involves the relationship between the difficulties of phase A children and the factors that influence them, as well as what strategies the teacher uses to overcome these difficulties.